Innovation: The Key Factor of Competitiveness for Chinese SMEs - Luo, Murong; Hussein Al-Shami, Samer Ali; Binti Mansor, Nusaibah (Opción, 2019)
Purpose-This study aims to present an overview of SMEs’ innovation in China, to identify the main problems, and provide practical suggestions. Design/methodology/approach-The research of this paper is based on the collection and evaluation of existing literature and survey reports. Findings-This study presents the general situation and characteristics of SMEs’ innovation in China, and concludes the main reason that hinders Chi- nese SMEs’ innovation is the lack of human resources, capital, innovation culture and information. Practical implications-This study suggests that, in addition to improving resources and environment, SMEs can also try to adopt micro-innovation to promote innovation activities. These suggestions are practical and can help SMEs maintain competitiveness. Originality/ value-This study provides an overview of Chinese SMEs’ innovation, which can be the basis for future research in this area.